Modelling of Escherichia coli in The Serin River, Serian Using The QUAL2K Model - Lim, Swee Wee (Universiti Malaysia Sarawak, UNIMAS, 2010)
Serin River is an important river because it is a source of drinking water and is used for recreation by the villagers. Hence, the objectives of this study were to determine the impact of different land uses on the faecal bacteria concentration and to determine the suitability and reliability of QUAL2K model to predict faecal bacteria concentration in the river water. A total of 8 trips were made from September 2009 till March 2010 with 5 stations along the main river and 4 tributaries that were studied. Results of analysis showed that tributaries that received pig farm effluent recorded significantly higher mean concentration of Escherichia coli (E. coli) of 3.31 log CFU/mL and total suspended solids (TSS) of 57 mg/L. Present study also showed that there is significant correlation between E. coli concentration and TSS. According to the NWQS, all the stations fell into Class III and Class IV based on E. coli concentration. The model was calibrated and validated using field data from October 2009 to March 2010. The prediction results showed that for the river water to be suitable as drinking water source, no E. coli contamination should be discharged from the headwater and from Sg. Bukah. As for the suitability of river water for recreational purposes, the maximum recommended concentration of E. coli allowed for the headwater, SB, SP and SR; were <400 CFU/100mL, <900 CFU/100mL, <1000 CFU/100mL and <380 CFU/100mL respectively during low tide, and during high tide, maximum concentration of E. coli allowed were <400 CFU/100mL, <1600 CFU/100mL, <2500 CFU/100mL and <510 CFU/100mL respectively. It is recommended that further studies be conducted on monitoring water quality by using models to ensure long term planning and sustainability use of river water.